Complementary and Alternative Medicine in Brazil: one concept, different meanings - Nelson Filice de Barros; Everardo Duarte Nunes
This article discusses the various meanings ascribed to the concept of Complementary and Alternative Medicine (CAM) in Brazil, where research on this theme has a limited tradition in terms of influences from anthropology, sociology of knowledge and epistemology, and sociology of CAM and clinical medicine. By means of the concepts identified in the literature, we elaborated a table with types of meanings. The terms Alternative Medicine and Complementary Medicine were found in more than one of the types in the table. Alternative Medicine identifies a model of medical practice influenced by the social, political, and economic context and by the logic of scientific production based on opposing pairs. Beginning in the 1980s, the important volume of reflections on official medical practice and the search for other forms of knowledge production led to the creation of the concept of Complementary Medicine. Its meaning is that of a new epistemological form of knowledge production between the official and alternative poles, a set of therapeutic practices, and confusion with the nomenclature for ancillary medical diagnostic tests, referred to in Portuguese as "complementary exams".